Inhibition and activation by CD244 depends on CD2 and phospholipase C-gamma1. - Clarkson, N; Brown, M (2009)
Regulation by the NK and T cell surface receptor CD244 in mice and humans depends both on engagement at the cell surface by CD48 and intracellular interactions with SAP and EAT-2. Relevance to human disease by manipulating CD244 in mouse models is complicated by rodent CD2 also binding CD48. We distinguish between contributions of mouse CD244 and CD2 on engagement of CD48 in a mouse T cell hybridoma. CD2 and CD244 both contribute positively to the immune response as mutation of proline-rich motifs or tyrosine motifs in the tails of CD2 and CD244, respectively, result in a decrease in antigen-specific interleukin-2 production. Inhibitory effects of mouse CD244 are accounted for by competition with CD2 at the cell surface for CD48. In humans CD2 and CD244 are engaged separately at the cell surface but biochemical data suggest a potential conserved intracellular link between the two receptors through FYN kinase. We identify a novel signaling mechanism for CD244 through its potential to recruit phospholipase C-gamma1 via the conserved phosphorylated tyrosine motif in the tail of the adaptor protein EAT-2, which we show is important for function.